Pengaruh Latihan Lari Interval Terhadap Kecepatan Lari Pada Pemain Sepak Bola Di Sekolah Sepak Bola Rukun Agawe Santosa (RAS) Klaten - NA'IMA, Aisyah Lifsantin; , Yulisna Mutia Sari, SSt.FT., M.Sc (); , Wahyuni, S.Fis., M.Kes (2015)
Background: Speed is a person's ability to perform a movement that is carried out continuously in the shortest possible time. At 50 meters running speed profile football players RAS Klaten measured using a stopwatch that has an average of 8.35 seconds with a classification that is moderate. One of exercise that is used to increase the speed of running is running interval training. Objective: To determine the effect running interval training on running speed of the the football players in school soccer RAS Klaten. Methods: The study was a quasi experiment with pre and post test without control group design. All samples submitted inclusion criteria given running interval training for 4 weeks with a frequency 3 times a week. Speed measurement made with a run of 50 yards using parameters such as a stopwatch. Data were analyzed using Wilcoxon test to test the effect of running interval training on running speed. Results: There was an effect running interval training on running speed of the football players in School Football RAS Klaten after the statistical test using wilcoxon match pair test with values obtained significance (2-tailed) 0.000. Conclusion: There was an effect running interval training on running speed of the football players in School Football RAS Klaten.